“Estrutura da Celula Nervoza”, by Bruno Lobo and Gaspar Vianna (1908): a pioneering work on Brazilian Neuroscience - Bruno Lopes SANTOS-LOBATO; José Eymard Homem PITTELLA (Arquivos de Neuro-Psiquiatria)
ABSTRACT Currently, the scientific production in Neuroscience in Brazil is very rich, but, historically, it has been scarce at first. The aim of this study is to present the work “Estrutura da Celula Nervoza”, by Bruno Lobo and Gaspar Vianna (1908), as a pioneering work for Brazilian science.